2021
DOI: 10.1080/10717544.2021.2009937
|View full text |Cite
|
Sign up to set email alerts
|

Novel optimized drug delivery systems for enhancing spinal cord injury repair in rats

Abstract: Effective and accurate delivery of drugs to tissue with spinal cord injury (SCI) is the key to rehabilitating neurological deficits. Sustained-release microspheres (MS) have excellent degradability and can aid in the long-term release of drugs. However, the burst release phenomenon can cause unexpected side effects. Herein, we developed and optimized an injectable poly(lactic-co-glycolic acid) (PLGA) MS loaded with melatonin(Mel), which were mixed further with Laponite hydrogels (Lap/MS@Mel, a micro-gel compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In addition, melatonin can be used in combination with various treatment methods to treat SCI. For instance, polylactic acid glycolic acid copolymer sustained-release microspheres with melatonin and laponite hydrogel for mixed injection to treat SCI ( Zhang M. et al, 2021 ). The use of melatonin in extracellular vesicles of stem cells reduces the levels of N6 methyladenosine modification (m6A) and methyltransferase 3 (METTL3) in SCI, and enhances the stability of USP29mRNA in MSCs, which also promote stem cell proliferation, differentiation, neurosphere formation and secretion of neurotrophic factors ( Li et al, 2017 ; Zheng et al, 2017 ).…”
Section: The Relationship Between Spinal Cord Injury and Melatoninmentioning
confidence: 99%
“…In addition, melatonin can be used in combination with various treatment methods to treat SCI. For instance, polylactic acid glycolic acid copolymer sustained-release microspheres with melatonin and laponite hydrogel for mixed injection to treat SCI ( Zhang M. et al, 2021 ). The use of melatonin in extracellular vesicles of stem cells reduces the levels of N6 methyladenosine modification (m6A) and methyltransferase 3 (METTL3) in SCI, and enhances the stability of USP29mRNA in MSCs, which also promote stem cell proliferation, differentiation, neurosphere formation and secretion of neurotrophic factors ( Li et al, 2017 ; Zheng et al, 2017 ).…”
Section: The Relationship Between Spinal Cord Injury and Melatoninmentioning
confidence: 99%
“…The common delivery routes for nanomedicine targeting spinal cord pathology are intravenous, intrathecal, intranasal, or intraspinal administration. Nanoparticles can be administered intravenously to allow for systemic distribution throughout the body and potential transport across the B-SCB [12,45,49,50,[85][86][87][88][89][90][91][92][93][94]. Gao et al demonstrated that intravenously administered nanoparticles are localised preferentially and dose-dependently at the lesion site in the spinal cord.…”
Section: Nanoneuropharmacologymentioning
confidence: 99%
“…Zhang et al developed and optimized injectable PLGA MS loaded with melatonin (Mel), which was further mixed with Laponite hydrogel to form a composite hydrogel scaffold to reduce the sudden release of MS. The MS was able to achieve stable and prolonged Mel release as well as synergistic Lap hydrogel to repair neural function in SCI by in situ injection ( Zhang et al, 2021 ).…”
Section: Application Of Hydrogels In Sci Repairmentioning
confidence: 99%